Selective Averaging of Evoked Potentials using Trajectory-Based Clustering - Jansen, B. H.; Nyberg, H. N.; Zouridakis, G. (Methods of Information in Medicine, 1994)
A clustering method has been developed to group evoked potentials that display similar prestimulus dynamic behavior. The procedure involves using the method of time delay embedding to construct a trajectory in state space from a time series. Certain features that characterize the geometry of the trajectory have been defined. The trajectory-based clustering algorithm has been applied to visual evoked potentials to determine relationships between prestimulus EEG and evoked potential shape.
Keywords: Evoked Potentials; Selective Averaging; Nonlinear Dynamics